MANAJEMEN PENDIDIKAN PONDOK PESANTREN PENDEKATAN EMPOWERMENT ENTREPENEURSHIP - Imron Rosady ('Ibadatuna : Jurnal Pengabdian Masyarakat, 2022)
The article describes the empowerment of entrepreneurial students in the Miftahul Ulum Islamic Boarding School Lumajang Cooperative Research using the Participatory Learning and Action (PLA) method and collecting secondary and primary data through direct data surveys to PPMU Baked Lumajang in Banyu Putih Kidul Village, Kec. Jatiroto Kab. Lumajang. Based on the results of the study, the empowerment of students in the cooperative unit of the Miftahul Ulum Islamic boarding school Lumajang has carried out the following activities: entrepreneurial guidance/education for students, counseling/cooperative education for the pesantren business sector, counseling/education on entrepreneurial organization, counseling/on implementation entrepreneurial education in strategy in marketing units)